Implementation Of The Srikandi Application In Supporting The Management Information System And Administration Of Correspondence In The Administration Section At The Surakarta Central General Hospital - Yuliatmojo, Widyantoro; Utami, Anita Tri; Pramuktisari, Nindita; Munawar, Muslim (Jurnal Multidisiplin Sahombu, 2025)
In the Circular Letter of the Secretary General of the Ministry of Health of the Republic of Indonesia number: HK.02.02/III/15086/2021, it is stated that every Central Work Unit/Technical Implementation Unit within the Ministry of Health must use the Electronic Official Manuscript Management Application (TNDE) for managing incoming and outgoing official manuscripts, including providing dispositions and checking outgoing official manuscripts. The application in question is Srikandi which is expected to provide better correspondence results so that information can be conveyed optimally. This study was located in the Administration Section of the Surakarta Central General Hospital. This study is descriptive and uses qualitative techniques to explain the adoption of the Srikandi application in facilitating the management information system and administrative communication in the administration section of the Surakarta Central General Hospital. Data collection methods include interviews, observations, and documentation. This study uses a triangulation approach for data validation. From the results of the study, it was found that the implementation of the Srikandi application in supporting the management information system and administrative correspondence of the administration section was quite good, although there were still user units who did not understand this application. Users are expected to open this application as often as possible so that information is not obstructed and correspondence services are better.